The Effects of Lactococcus garvieae and Pediococcus pentosaceus on the Characteristics and Microbial Community of Urtica cannabina Silage - Yongcheng Chen; Shuangming Li; Yingchao Sun; Yuxin Chai; Shuan Jia; Chunhui Ma; Fanfan Zhang (Microorganisms, 2025)
The utilization of nettle (Urtica cannabina) as feed is restricted by its material properties (antibacterial activity and high buffering capacity). This study hypothesized that the use of lactic acid bacteria (LAB) attached to nettles can improve these problems. Lactococcus garvieae (LG), Pediococcus pentosaceus (PP), and LG + PP (LP) isolated from nettles were inoculated into nettle silage to explore nutrient retention and the microbial community structure. The results showed that inoculation significantly delayed dry matter and crude protein loss, inhibited neutral detergent fiber and acid detergent fiber degradation, and reduced ammonia nitrogen (NH3-N) accumulation. There was a significant increase in Firmicutes abundance after inoculation, and the dominant genus, Aerococcus, was negatively correlated with NH3-N accumulation. In the later stages of the PP treatment, Atopistipes synergistically inhibited Clostridia with acetic acid. However, the high buffering capacity and antibacterial components of raw nettle led to increased pH values during the later fermentation stages, limiting sustained acid production by LAB. These results confirm that nettle-derived LAB can effectively improve the quality of silage by regulating the microbial community and the acidification process; however, they must be combined with pretreatment strategies or optimized composite microbial agents to overcome raw material limitations. This study provides a theoretical basis and technical support for the utilization of nettle as feed.